Point-of-care testing and INR within-subject variation in patients receiving a constant dose of vitamin K antagonist - van den Besselaar, A M H P; Biedermann, Joseph S; Kruip, Marieke J H A (Thrombosis and haemostasis, 2015)
Many patients treated with vitamin K antagonists (VKA) determine their INR using point-of-care (POC) whole blood coagulation monitors. The primary aim of the present study was to assess the INR within-subject variation in self-testing patients receiving a constant dose of VKA. The second aim of the study was to derive INR imprecision goals for whole blood coagulation monitors. Analytical performance goals for INR measurement can be derived from the average biological within-subject variation. Fifty-six Thrombosis Centres in the Netherlands were invited to select self-testing patients who were receiving a constant dose of either acenocoumarol or phenprocoumon for at least six consecutive INR measurements. In each patient, the coefficient of variation (CV) of INRs was calculated. One Thrombosis Centre selected regular patients being monitored with a POC device by professional staff. Sixteen Dutch Thrombosis Centres provided results for 322 selected patients, all using the CoaguChek XS. The median within-subject CV in patients receiving acenocoumarol (10.2 %) was significantly higher than the median CV in patients receiving phenprocoumon (8.6 %) (p = 0.001). The median CV in low-target intensity acenocoumarol self-testing patients (10.4 %) was similar to the median CV in regular patients monitored by professional staff (10.2 %). Desirable INR analytical imprecision goals for POC monitoring with CoaguChek XS in patients receiving either low-target intensity acenocoumarol or phenprocoumon were 5.1 % and 4.3 %, respectively. The approximate average value for the imprecision of the CoaguChek XS, i. e. 4 %, is in agreement with these goals.